Contractual Frictions and the Margins of Trade - Azomahou, Theophile T. (World Bank, Washington, DC, 2018)
A growing body of work has shown that the quality of national institutions that enforce written contracts plays an important role in shaping a country's comparative advantage. Using highly disaggregated bilateral and unique harmonized firm-level trade data across a large number of countries, this paper contributes to this literature by providing a comprehensive analysis of the mechanisms through which institutional frictions affect the pattern of aggregate trade flow, distinguishing the effects on the intensive and extensive margins. The analysis finds that contractual friction distorts countries' trade pattern beyond its effect on domestic production structure, by deterring the probability of exporting (the extensive margin) and export sales after entry (the intensive margin), particularly in industries that rely more heavily on relationship-specific inputs (more vulnerable to holdup problems). The analysis also finds that contractual frictions matter more for the intensive margin than the extensive margin of exporting. In addition, better contracting institutions increase the probability of survival of new export products in more contract-intensive industries. These results have important policy implications for developing countries that seek to boost export growth but many of which suffer from poor contracting institutions.